2015
DOI: 10.1152/ajpheart.00283.2015
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage depletion lowers blood pressure and restores sympathetic nerve α2-adrenergic receptor function in mesenteric arteries of DOCA-salt hypertensive rats

Abstract: Thang LV, Demel SL, Crawford R, Kaminski NE, Swain GM, Van Rooijen N, Galligan JJ. Macrophage depletion lowers blood pressure and restores sympathetic nerve ␣ 2-adrenergic receptor function in mesenteric arteries of DOCA-salt hypertensive rats. Am J Physiol Heart Circ Physiol 309: H1186 -H1197, 2015. First published August 28, 2015; doi:10.1152/ajpheart.00283.2015.-We tested the hypothesis that vascular macrophage infiltration and O 2 Ϫ release impairs sympathetic nerve ␣ 2-adrenergic autoreceptor (␣2AR) funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 72 publications
5
30
0
Order By: Relevance
“…The finding that macrophages can be active secretors of catecholamines is important as macrophage infiltration of tissues commonly occurs in obesity (Weisberg et al, ). Superoxide generated from infiltrating macrophages disrupts normal pre‐synaptic α 2 ‐adrenoceptor function, increasing the release of NA from the nerves, a mechanism that elevates blood pressure (Thang et al, ). Thus, macrophage infiltration in PVAT may influence NA release and blood pressure in disease.…”
Section: Catecholamine Release and Synthesis By Adipose Tissuementioning
confidence: 99%
“…The finding that macrophages can be active secretors of catecholamines is important as macrophage infiltration of tissues commonly occurs in obesity (Weisberg et al, ). Superoxide generated from infiltrating macrophages disrupts normal pre‐synaptic α 2 ‐adrenoceptor function, increasing the release of NA from the nerves, a mechanism that elevates blood pressure (Thang et al, ). Thus, macrophage infiltration in PVAT may influence NA release and blood pressure in disease.…”
Section: Catecholamine Release and Synthesis By Adipose Tissuementioning
confidence: 99%
“…In DOCA-salt hypertensive rats, the mineralocorticoid derivative DOCA and salt loading increase splanchnic and renal SNA (4,40,90,91). Several studies have suggested that DOCA-salt hypertension development and sympathetic hyperactivity in these vascular beds involve oxidative stress and immune system activation (4,81,91).…”
Section: Introductionmentioning
confidence: 99%
“…The prejunctional ␣ 2 -adrenergic receptor (␣ 2 AR) inhibits NE release by coupling via G␣ i/o proteins to inhibit voltage-gated N-type Ca 2ϩ channels that control NE release (35,77). This negative feedback regulates sympathetic tone and prevents sustained increases in blood pressure (55,81). Of the three ␣ 2 ARs, ␣ 2A AR and ␣ 2C AR couple to feedback inhibition of NE release; ␣ 2A AR is predominant at higher levels of SNA (33).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations